The Main Problems Associated with Teaching English Technical Vocabulary - Mukhammadieva Shakhzoda Farkhodovna (International Journal on Integrated Education, 2023)
The aviation industry has now reached considerable heights: there is a growing need to build aircraft to meet the needs of an increasingly mobile public seeking quick and easy ways to get around the world. As passenger numbers rise, so do the numbers of airlines and airports that are providing the fastest mode of transport for the travelling public. In addition to this, there is a growing need to hire employees in this field - flight attendants, air traffic controllers, pilots, etc.., and this fact demonstrates the importance and significance of the aviation sector, which has remained undervalued in recent times. This study aims to identify the problems in the teaching of English in aviation. Because of the large amount of terminology and special phrases that are used in aviation English, we have attempted to analyse and identify what students should focus on vocabulary development as well as to identify the main problems in learning it.